Improvement of equivalent power consumption coding secure against power analysis attacks - WU Zhen; CHEN Yun; WANG Min; CHEN Jun (Tongxin xuebao)
Equivalent power consumption coding algorithm not only could improve algorithm efficiency,but also could be against the power analysis attacks.But it had weaknesses in all-zero exponential segment because of a defect of pseudo-operation design.So a new pseudo-operation was proposed to improve the algorithm’s security.And a rapid im-plementation using Montgomery algorithm was presented too.It could accelerate the operation with no-lower safety.The research’s validity is proved in the real power testing platform.